Directly Modulated Single‐Mode Tunable Quantum Dot Lasers at 1.3 µm. Issue 3 (5th February 2020) - Wan, Yating; Zhang, Sen; Norman, Justin C.; Kennedy, MJ; He, William; Tong, Yeyu; Shang, Chen; He, Jian‐Jun; Tsang, Hon Ki; Gossard, Arthur C.; Bowers, John E.
Abstract: Wavelength tunable lasers are increasingly needed as key components for wavelength resource management technologies in future dense wavelength division multiplexing (DWDM) systems. While material systems with multiple quantum wells as an active region are widely used in long‐wavelength tunable lasers, the unique advantages of InAs/GaAs quantum dots (QDs) for low‐power operation, excellent thermal stability, and wide spectral bandwidth may open a new avenue in this field. Combining the advantages of QDs with a special designed half‐wave coupled cavity structure, directly modulated, single‐mode, tunable InAs/GaAs QD lasers are demonstrated at 1.3 µm wavelength range. The half‐wave coupler provides an active–active coupled‐cavity tunable structure without involving gratings or multiple epitaxial growths, producing synchronous power transfer in the two output waveguides and high single‐mode selectivity. 27‐channel wavelength switching is achieved with side‐mode‐suppression‐ratio of around 35 dB. Under continuous‐wave electrical injection, over 9 mW output power can be measured with 716 kHz Lorentzian linewidth, 4 GHz 3‐dB bandwidth, and 8 Gbit s −1 non‐return‐to‐zero signal modulation by directly probing the chip. Abstract : The first single‐mode tunable InAs/GaAs quantum dot (QD) lasers at 1.3 µm are demonstrated. Without involving gratings or multiple epitaxial growths, 27‐channel wavelength switching is achieved with side‐mode‐suppression‐ratio of around 35 dB. Over 9 mW output power can be measured under continuous‐wave electrical injection, with 716 kHz Lorentzian linewidth, 4 GHz 3‐dB bandwidth, and 8 Gbit s −1 non‐return‐to‐zero signal modulation.